Biochar amendment decreases soil microbial biomass and increases bacterial diversity in Moso bamboo (Phyllostachys edulis) plantations under simulated nitrogen deposition. (9th April 2018) - Li, Quan; Lei, Zhaofeng; Song, Xinzhang; Zhang, Zhiting; Ying, Yeqing; Peng, Changhui
Abstract: Biochar amendment has been proposed as a strategy to improve acidic soils after overuse of nitrogen fertilizers. However, little is known of the role of biochar in soil microbial biomass carbon (MBC) and bacterial community structure and diversity after soil acidification induced by nitrogen (N) deposition. Using high-throughput sequencing of the 16S rRNA gene, we determined the effects of biochar amendment (BC0, 0 t bamboo biochar ha −1 ; BC20, 20 t bamboo biochar ha −1 ; and BC40, 40 t bamboo biochar ha −1 ) on the soil bacterial community structure and diversity in Moso bamboo plantations that had received simulated N deposition (N30, 30 kg N ha −1  yr −1 ; N60, 60 kg N ha −1  yr −1 ; N90, 90 kg N ha −1  yr −1 ; and N-free) for 21 months. After treatment of N-free plots, BC20 significantly increased soil MBC and bacterial diversity, while BC40 significantly decreased soil MBC but increased bacterial diversity. When used to amend N30 and N60 plots, biochar significantly decreased soil MBC and the reducing effect increased with biochar amendment amount. However, these significant effects were not observed in N90 plots. Under N deposition, biochar amendment largely increased soil bacterial diversity, and these effects depended on the rates of N deposition and biochar amendment. Soil bacterial diversity was significantly related to the soil C/N ratio, pH, and soil organic carbon content. These findings suggest an optimal approach for using biochar to offset the effects of N deposition in plantation soils and provide a new perspective for understanding the potential role of biochar amendments in plantation soil.